Creative Tourism as the Key to Community Empowerment: Revitalizing Local Narratives through Cultural Performances at Prambanan Temple - ramadhan19; Muhammad Zikri , Muhammad Zikri (Rumah Jurnal UNEJ, 2025)
This study examines the role of creative tourism in empowering local communities surrounding Prambanan Temple, focusing on cultural performances as vehicles for revitalizing local narratives. Using a case study approach with mixed methods data collection, the research demonstrates how cultural performances serve as bridges between heritage preservation and contemporary community development. Findings indicate that creative tourism initiatives centered around authentic cultural performances have significantly increased community participation, economic benefits, and cultural pride. The study reveals a three-fold impact: economic diversification, strengthened social cohesion, and the preservation of intangible cultural heritage. These results suggest that creative tourism frameworks can be effectively leveraged to transform heritage sites from passive tourist attractions into dynamic spaces of cultural exchange and community revitalization, providing valuable insights for other heritage destinations seeking sustainable tourism development models